Short Course Androgenisation in Late Reported Cases with Microphallus - Mahmudul Huque; Tania Tofail; Tofail Ahmed (Highlights on Medicine and Medical Research Vol. 4, 2021)
Background and Objectives: Microphallus is an abnormally short penis and its management should begin in infancy or in early childhood. The present study investigated the response of short term testosterone therapy in late reported cases of microphallus. Methods: A total of 17 cases of microphallus between the age of 8 and 15 years were studied. Standard criteria for the diagnosis of microphallus were followed among the individual with bilateral palpable gonad. All cases were treated with intramuscular testosterone 50 to 75 mg once every 21 days until their average stretched penile length (SPL) for age is achieved or total dose of 450 mg of testosterone is given. Response to testosterone treatment was measured by the absolute and percent increment in SPL. We also compared the response of treatment of cases reported up-to age of 10 years and thereafter. Results: A total of 17 cases were included in the study. All of them achieved target SPL. Out of total 17 boys, 7 were between 8 to 10 years (Group 1) and 10 were between 12 to 15 years (Group 2) of age. The pre-treatment SPL of 17 microphallus cases was 3.13±0.15 (2.81 - 3.45 cm). All the cases achieved average phallus for the age with a significant increased post- treatment SPL of 8.94±0.32 (8.27 -9.61 cm); sig. .000. The two groups had similar gain in SPL (3.89 -6.25) vs (5.32 -7.34 cm) & % increment (126.47 -215.31%) vs (145.43 -288.53%) (sig. ? .139) but total testosterone required in older boys (Gr 2) was higher (162.52 –387.48 mg) vs (326.vs 15 – 433.85 mg); sig.0.043. Conclusion: Microphallus in boys with palpable gonads responded to short term testosterone treatment in late reported cases also and we termed these cases as simple microphallus.